2019
DOI: 10.1136/bmjopen-2018-023376
|View full text |Cite
|
Sign up to set email alerts
|

Local patterns of social capital and sustenance of the Community-Based Health Planning Services (CHPS) policy: a qualitative comparative study in Ghana

Abstract: ObjectiveSocial capital—the resources embedded in social relationships—has been associated with health severally. Notwithstanding, only a handful of studies have empirically examined how it shapes health policies. This paper extends the discourse by comparatively examining how variations in local patterns of structural and cognitive social capital underpin the successes and challenges in managing and sustaining the Community-Based Health Planning Services (CHPS) policy in Ghana. The CHPS is an intervention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The theme of healthcare service problems suggests that long distances and transportation costs, unsympathetic nursing staff, mistreatment, and limited stocks of medication impact young mothers. A growing body of literature has also revealed that barriers in accessing maternal and child healthcare services include distant geographical locations, long travelling periods, expensive transportation, and healthcare workers' negative attitudes [70][71][72][73]. Limited stocks of medication (or stock-out) has particularly been noted in several South African health districts [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theme of healthcare service problems suggests that long distances and transportation costs, unsympathetic nursing staff, mistreatment, and limited stocks of medication impact young mothers. A growing body of literature has also revealed that barriers in accessing maternal and child healthcare services include distant geographical locations, long travelling periods, expensive transportation, and healthcare workers' negative attitudes [70][71][72][73]. Limited stocks of medication (or stock-out) has particularly been noted in several South African health districts [74].…”
Section: Discussionmentioning
confidence: 99%
“…Limited stocks of medication (or stock-out) has particularly been noted in several South African health districts [74]. Sumankurro [70] argues that running out of medication is a barrier to optimal maternal and child healthcare services in low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…36 Geographical locations and the costs of transport are also barriers to maternal and child healthcare in low and middle income countries. [38][39][40] The current study found that girls' preference for using traditional healers was also a factor that affected their willingness to access healthcare services. The preference for using traditional healers is often cited in the literature [41][42] as approximately 80% of people in Africa use traditional medication, especially for maternal and reproductive health issues.…”
Section: Discussion 25mentioning
confidence: 67%
“…A growing body of literature has also revealed that barriers in accessing maternal and child healthcare services include distant geographical locations, long travelling periods, expensive transportation, and healthcare workers' negative attitudes. [63][64][65][66] Limited stocks of medication (or stock-out) has particularly been noted in several South African health districts. 67 Sumankurro 63 argues that running out of medication is a barrier to optimal maternal and child healthcare services in low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66] Limited stocks of medication (or stock-out) has particularly been noted in several South African health districts. 67 Sumankurro 63 argues that running out of medication is a barrier to optimal maternal and child healthcare services in low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%